Revisiting the lectotype of Rhamnus micranthus (Rhamnaceae) - Garwood, Nancy C. (Phytotaxa, 2016)
The lectotypes of Rhamnus micranthus, the basionym of Trema micrantha, proposed by Wijnands (1983), Howard (1988) and Jarvis (2007) are incomplete or incorrect. The source of the problem is discussed and a new lectotype is here designated.